Efficacy of Thymus vulgaris, Syzygium aromaticum, and Marrubium vulgare essential oils against multi-drug resistant uropathogenic bacteria - Abdelaziz Ait Melloul; Imane Abbad; Mustapha Barakate (E3S Web of Conferences)
Urinary tract infections represent significant global health concern, especially due to the emergence of multi-drug-resistant bacterial strains. This study investigates the antibacterial potential of essential oils (EOs) extracted from Thymus vulgaris, Syzygium aromaticum and Marrubium vulgare against multi-resistant uropathogenic bacteria. The chemical composition of the studied EOs was determined by gas chromatography-mass spectrometry (GC-MS), while their antibacterial activity was assessed using disc diffusion and broth microdilution assays. The obtained results indicated that the EOs from T. vulgaris and S. aromaticum exhibited the most potent antibacterial effects against all tested bacterial strains, with inhibition zones ranging from16 ± 0.05 mm to 35 ± 0.07 mm. Remarkably, T. vulgaris EO demonstrated the highest antibacterial activity, with an inhibition zone of 35 ± 0.13 mm. Furthermore, the minimum inhibitory concentrations (MIC) and the minimum bactericidal concentrations (MBC) values confirmed that the strong antibacterial potential of T. vulgaris and S. aromaticum EOs, with MICs ranging from 0.64 to 5.12 mg/mL and MBCs from 1.28 to 10.24 mg/mL. Both E. coli and Klebsiella spp. were particularly susceptible to the tested oils. GC-MS analysis of the most active EOs revealed that T. vulgaris was predominantly composed of thymol (42.34%), whereas S. aromaticum oil was primarily characterized by cinnamaldehyde (45.04%).